Why Has Nobody Told Me This Before? - Smith, Julie (New York HarperCollins, 2022)
Filled with secrets from a therapist's toolkit, Why Has Nobody Told Me This Before teaches you how to fortify and maintain your mental health, even in the most trying of times. Dr Julie Smith's expert advice and powerful coping techniques will help you stay resilient, whether you want to manage anxiety, deal with criticism, cope with depression, build self-confidence, find motivation, or learn to forgive yourself. Why Has Nobody Told Me This Before tackles everyday issues and offers practical solutions in bite-sized, easy-to-digest entries which make it easy to quickly find specific information and guidance"
Includes Index
Keywords: Mental health., Life skills.Self-help techniques